6x + 1 /3 +1 = x-3/7
Answers
Answered by
1
Answer:
6x+1/3+1 = x-3/7
7(6x+1) = 3+1(x-3). [ by cross multiplication ]
42x+7 = 3+x-3
42x+7 = x
42x-x = 7
41x = 7
x = 7/41
thanks
Answered by
1
Answer:
x = -19 / 14
Step-by-step explanation:
⇒ ![\frac{6x + 1 }{3 +1} = \frac{7x - 3}{7} \frac{6x + 1 }{3 +1} = \frac{7x - 3}{7}](https://tex.z-dn.net/?f=%5Cfrac%7B6x+%2B+1+%7D%7B3+%2B1%7D+%3D+%5Cfrac%7B7x+-+3%7D%7B7%7D)
⇒ ![7(6x+1) = 4(7x-3) 7(6x+1) = 4(7x-3)](https://tex.z-dn.net/?f=7%286x%2B1%29+%3D+4%287x-3%29)
⇒ ![42x+7 = 28x - 12 42x+7 = 28x - 12](https://tex.z-dn.net/?f=42x%2B7+%3D+28x+-+12)
⇒ ![42x - 28x = -(7+12) 42x - 28x = -(7+12)](https://tex.z-dn.net/?f=42x+-+28x+%3D+-%287%2B12%29)
⇒![14x = -19 14x = -19](https://tex.z-dn.net/?f=14x+%3D+-19)
⇒![x = \frac{-19}{14} x = \frac{-19}{14}](https://tex.z-dn.net/?f=x+%3D+%5Cfrac%7B-19%7D%7B14%7D)
HOPE THIS HELPS ✌️✌️
PLEASE MARK AS THE BRAINLIEST IF THAT HELPS
Similar questions